Motivasi Hidup Lansia Yang Kehilangan Pasangan Di Kabupaten Malang - Shita Resti Maheswari; Zahwa Maghfirotul Wahyudi; Chariesma Amelia Putri; Riyan Rahmat Aminullah Basith; Edy, Dewi Fatmasari (Universitas Negeri Malang, 2023)
Elderly is a final human development process that is vulnerable to physical, cognitive, and emotional changes so it is necessary to increase motivation in life. Life motivation can be developed through oneself and family social support, especially partners. If there is no partner as social support, then the elderly can experience a decrease in motivation to live which has an impact on mental health and well-being. This study aims to determine the level of motivation of the elderly who have lost their spouse because their partner has passed away. This study uses Goal Setting Motivation. This research method uses qualitative methods with a phenomenological approach. Methods of data collection using the approach of observation and semi-structured interviews. The number of participants in this study were four people in the category of two elderly widows and two elderly widowers who live in Kabupaten Malang. The results obtained are that motivation in the elderly is based on the existence of children and grandchildren and optimism to live longer.